Development of energy-efficient building environmental quality evaluation framework - Ng, Ban Huat (2013)
This research is about the development of an energy-efficient building environmental quality evaluation framework for office building in hot and humid climatic regions. The aim of this research is to develop an evaluation framework for the identification of problems with respect to energy-efficient design affecting occupants’ comfort. This research focuses on the application of energy-efficient design in office building; secondly, identifies the effects of energy-efficient design problems towards occupants’ comfort; and finally proposes an evaluation framework for the rating of energy-efficient design problems which affect the occupants’ comfort. This research was conducted at three energy-efficient buildings in Malaysia. A new building performance evaluation framework Energy-efficient Building Environmental Quality Evaluation Framework has been constructed and tested at the selected energyefficient buildings.